ELEMEN BUDAYA DI KAMPUNG CIREUNDEU SEBAGAI JEMBATAN DALAM KOMUNIKASI ANTAR UMAT BERAGAMA - Wawan Setiawan; Ghina May Sandy; Erin Alvianita (STAINU Tasikmalaya, 2023)
The Cireundeu indigenous people are a social system that has its own belief system, value system, system of norms and symbols. These four systems face the pressure of continuity and discontinuity when there is parochialization of Islamic traditions and modernity. The strong currents of parochialization have made the Cireundeu people more adaptive to Islamic culture at the symbolic level. This can be seen in the inclusion of Islam as a religion in their ID cards. On the other hand, they are still able to maintain and continue their beliefs, values ​​and norms. As for their attitude towards the parochialization of modernity, it turns out to be broader, except in religion. This research method is to use a descriptive analysis method with a qualitative approach. The researcher analyzes and describes according to the events seen through observation and what is obtained through interviews and the documents obtained. Qualitative research to present a realistic picture of behavior or events, to answer questions and to help understand human behavior. The results of this study indicate that Kampung Cireundeu, which is located in the Cimahi area, Leuwi Gajah sub-district, South Cimahi sub-district, has two religions, namely Islam and belief (Sunda Wiwitan). These two religions live side by side, this has an impact on the development of da'wah in Cireundeu village. The graph of the development of da'wah in the Cireundeu traditional village continues to grow from year to year, although the development is still in terms of quantity, not quality. Cirendeu Traditional Village is a reconstruction of the traditional Sundanese way of life. If you pay close attention, you will find various uniqueness in Cirendeu Village. This starts from living with kokolot, Sundanese artists, until you will find mothers pounding rice in saung lisung, cooking with firewood in hawu, watching farmers grow crops, and learning traditional Sundanese arts and how to process cassava into a staple food. . Based on this, it cannot be denied that Kampung Cirendeu is an alternative tourist spot that provides various tourism options with the atmosphere of traditional Sundanese agrarian life. Based on these criteria, the Cimahi City Government made Kampung Cirendeu a cultural tourism destination.